An experience sampling study of expressing affect, daily affective well‐being, relationship quality, and perceived performance. Issue 4 (30th June 2014) - Daniels, Kevin; Glover, Jane; Mellor, Nadine
<x xml:space="preserve">Abstract</x> Few studies have directly examined the processes through which workers use job resources, such as job control and social support, to regulate affect. We focused on affective expression, which is a specific form of affect regulation. We investigated the extent to which workers used both job control and social support to express affect. Thirty‐nine call centre workers provided data up to four times a day over five consecutive working days (number of observations = 272). Executing job control to allow workers to express affect was related to using social support to express affect. Workers' understanding of their personal goals mediated relationships between using social support to express affect and four outcomes (negative affect, positive affect, perceived performance, and quality of workplace relationships). Perceived empathy mediated relationships between using social support to express affect and three outcomes (negative affect, positive affect, and quality of workplace relationships). The findings indicated that (1) one job resource can be used to facilitate using another job resource for affect regulation and (2) different job resources may play different roles in conferring benefits from affective expression. Practitioner points Jobs cannot be treated as static entities with fixed characteristics. Rather workers will use resources embedded in job design for specific purposes. Job redesign interventions intended to enhance affective well‐being need to take account of the social and cognitive processes that mediate the relationship between work and affective well‐being. Job redesign interventions need to integrate information about dynamic processes in which use of one job resource can enable use of another job resource.